Metabolome and transcriptome profiling reveal new insights into somatic embryo germination in Norway spruce (Picea abies). (28th June 2017) - Dobrowolska, Izabela; Businge, Edward; Abreu, Ilka N; Moritz, Thomas; Egertsdotter, Ulrika
Abstract: Transcriptome, metabolome and histological profiling were performed on normal and aberrant somatic embryo germinants of Norway spruce ( Picea abies L. Karst) providing a simplistic systems biology description of conifer germination. Aberrant germinants (AGs) formed periderm-like tissue at the apical pole and lacked shoot growth above the cotyledons. Transcriptome profiling (RNA-Sequencing) revealed a total of 370 differentially expressed genes at ≥1 or ≤−1 log2 -fold change, where 92% were down-regulated in AGs compared with normal germinants (NGs). Genes associated with shoot apical meristem formation were down-regulated in AGs, or not differentially expressed between AGs and NGs. Genes involved in hormone signaling and transport were also down-regulated. Metabolite profiling by gas chromatography–mass spectrometry (MS) and liquid chromatography–MS revealed biochemical difference between AGs and NGs, notably increased levels of sugars including glucose in AGs. Genes involved in glucose signaling were down-regulated and genes involved in starch biosynthesis were up-regulated, suggesting involvement of sugar signaling during late embryo development and germination. The overall results provide new data enabling further studies to confirm potential markers for a normal germination process in conifers.